PERBEDAAN PRODUKTIVITAS LEGUMINOSE RAWA DI DANAU PANGGANG KALIMANTAN SELATAN SEBAGAI HIJAUAN PAKAN - T. Rostini (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2015)
Legume forages is one ingredient that is absolutely necessary either quantitatively or qualitatively throughout the year in livestock production systems. The purpose of this study was to analyze and evaluate the productivity and quality of swamp Legume nutrients South Kalimantan Methods survey by taking samples for identification, production levels BK, Important Value Index and carrying capacities legumes. The results showed in swamplands have 10 types of potential leguminose which has an important index values and capacities are 1.7 ST ha . Concluded legume swamp can be used for ruminant feedKey words : carrying capacity, dominant, productivity. legume,